Algorithms to minimize total completion time in a two-machine flowshop problem with uncertain set-up times. Issue 8 (3rd August 2021) - Aydilek, Harun; Aydilek, Asiye; Allahverdi, Ali
Abstract : The two-machine flowshop scheduling problem to minimize total completion time with separate set-up times is addressed. Set-up times are modelled as uncertain within an interval where only the lower and upper bounds are known. Eighty-one different versions of a newly developed constructive algorithm are proposed. Computational experiments to evaluate the performance of the proposed algorithm are conducted in two stages. In the first stage, 81 versions of the algorithm are compared with each other and the top seven versions are selected. In the second stage, the performances of the top seven versions are compared with the performance of the best existing known algorithm for the deterministic set-up times solution in the literature. The computational results reveal that errors of the top seven (out of 81) versions of the algorithm are less than 0.005. All computational results are statistically verified. Therefore, the proposed algorithm has excellent performance.